116k views
5 votes
Solve the Inequality:
(b)/(3) \geq -1

User Orange
by
5.0k points

1 Answer

5 votes


(b)/(3) \geq - 1 \\ = 3 * (b)/(3) \geq * ( -1 ) \\ = b \geq3 * ( - 1) \\ = b \geq - 3 * 1 \\ \\ = b \geq - 3

Step By Step Explanation:

  • Multiply both sides of the inequality by 3
  • Reduce the numbers with the greatest common factor 3
  • Multiplying a positive and a negative equals a negative
  • Any expression multiplied by 1 remains the same

☆彡Hanna

#CarryOnLearning

User Fabian Hueske
by
5.3k points